Childhood pemphigus foliaceus. Seborrheic variant. - Bonifazi, E.; Garofalo, L.; Pappalardi, M. (European Journal of Pediatric Dermatology, 2003)
The seborrheic variant of pemphigus foliaceus affects the seborrheic regions, mainly the scalp (1, 3), in absence of mucosal lesions. The erythematous variant is characterized by lesions on photoexposed areas and by IgG and C3 deposits both interkeratinocytic and at the dermal-epidermal junction. Overlap forms do exist as shown by our case. Histologically, there is superficial acantholysis with isolated keratinocytes level with the granular layer (2). The immunofluorescence shows a high pemphigus phenomenon and, sometimes, lupus erythematosus-like findings (4). The clinical differential diagnosis from impetigo and eczema is particularly difficult in children The prognosis is usually benign and the disorder can be sometimes controlled by topical corticosteroids.